Geomorphology of Climatically and Τectonically Sensitive Areas (Abstract Book) - Mutaqin, Bachtiar Wahyu (2019)
Volcanic materials from the 1257 CE eruption of Samalas volcano reached the sea and may have caused a pyroclastic density current-triggered tsunami since one of these crossed the Alas Strait and deposited its pumice fragments on the western coast of Sumbawa Island, Indonesia. However, the study of tsunami deposits following this eruption remains unknown, whereas the geomorphological impacts of this eruption on the island of Lombok are now better understood. The main goal of this study is, therefore, to investigate whether a tsunami had been triggered by the 1257 CE eruption of Samalas volcano. We collected and analyzed several samples of coral and seashells from tsunami deposits along the west coast of Sumbawa, i.e., in Belang Island and abandoned fishponds in Kiantar Village, in order to identify the tsunami sources and the occurrence period of these events. Based on radiocarbon dating of coral and seashell samples, we conclude that the 1257 CE eruption of Samalas volcano triggered a minor tsunami that hit Belang Island. Other tsunami deposits located in abandoned fishponds are dated 4th century CE and 9th century CE. We also conclude that a large earthquake triggered these tsunamis since no volcanic eruption occurred near the Alas Strait at that time that may trigger a tsunami.